Academy for Roblox pros. 1, Attack of the zombies - Shea, Louis (New York, NY : Graphix, an imprint of Scholastic, 2024)
Mitch and his friends thought that they were having an average day at school. Their principal, Principal Borelox, was being awful as usual, and Roger and his cronies were getting on their nerves. But when Mitch accidentally spills his drink on his computer in the tech lab, something miraculous happens. A door appears out of nowhere with the symbol of their favorite video game, Roblox. Well, Mitch and his buddies just have to check it out! Stepping through the door, the kids are immediately transported into Roblox Academy, a blocky world where they are all avatars of themselves. Can the kids get to the bottom of this digital world or will the mysterious villain, Mr. Warlock, turn them all into zombies!?
An unofficial Roblox graphic novel.
3-6
GN450L
Keywords: Roblox (Video game) -- Comic books, strips, etc; Roblox (Video game) -- Juvenile fiction; Students -- Comic books, strips, etc; Students -- Juvenile fiction; Friendship -- Comic books, strips, etc; Video games -- Comic books, strips, etc; Video games -- Juvenile fiction; Good and evil -- Comic books, strips, etc; Zombies -- Comic books, strips, etc; Zombies -- Juvenile fiction; Students -- Fiction; Friendship -- Fiction; Video games -- Fiction; Good and evil -- Fiction; Zombies -- Fiction; Adventure and adventurers. -- Fiction; Action and adventure comics; Graphic novels; Comics (Graphic works)